ACAA2 and FASN polymorphisms affect the fatty acid profile of Chios sheep milk - Symeou, Simoni; Tzamaloukas, Ouranios; Banos, Georgios; Miltiadou, Despoina (My University, 2020)
The objective of the research reported in this research communication was the identification and association of single nucleotide polymorphisms (SNP) in the ovine DGAT1, FASN, SCD1 and ACAA2 genes with milk fat percentage and fatty acid (FA) content. Three consecutive monthly milk samplings were obtained from a total of 429 purebred Chios ewes during mid-lactation. Genotypic data were jointly analyzed with 1184 fat content and 37 718 FA percentage records using mixed models. The 3' untranslated region (UTR) of the DGAT1 gene and the 5' and 3'UTRs of the SCD1 gene appeared to be monomorphic. The FASN g.14777C>T SNP on exon 31 was associated with C13:0 and the ACAA2 g.2982T>C SNP on the 3'UTR was associated with C9:0, C11:0, C12:1 cis-9, C13:0 and the ω6/ω3 index, while fat percentage was not affected by the identified SNPs. The results could be useful for breeding programs aiming to improve the quality and nutritional value of ovine milk.
Keywords: SCD1; ACAA2; DGAT1; FASN; fatty acids